Comparative CFD Analysis of Single-Stage and Two-Stage Entrained Flow Coal Gasifier for Different Firing Condition - Ramesh J. Bhangi; Devang A. Thakar (International Journal of Engineering and Management Research, 2023)
We describe here our progress toward developing high-filtering computational fluid dynamics (CFD) models of commercial-scale gasifiers for use in single-stage up and down flow and two-stage up-flow gasifier of fired condition in gasification process. Coal gasification process is regulated by several operating parameters. The type of coal gasifier and coal gasification process, the chemistry of coal gasification and classification of coal gasification process. The comparative of single-stage and two-stage entrained flow coal gasifier in different firing of performance enhancement. The exit temperature and exit mass flow rate is good for REI model and Petcoke and Illions #6 types of coal is to be tested for both the gasifier testing and found that Petcoke is better than Illions #6 in the process of single stage down flow gasifier. The carbon conversion and cold-gas efficiency is better forREI model and higher heating value (HHV) of syngas is DOE model. The gasifier performance is varied with length and found that when length of gasifier increases we will get better performance.